The Effect Of Motivation And Job Satisfaction On Performance With Commitment As An Intervening Variable Of Ptpn Ii Sei Semayang Employees - Deny Pratama; Yohny Anwar; Darmilisani Darmilisani (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze brand, facilities and service quality on customer satisfaction at Primadona Service Station. This study uses a quantitative method involving 65 employees as respondents. Data collection was carried out using questionnaires. The data obtained were analyzed using multiple PLS-SEM analysis with the Smart PLS 4 program. The results of this study indicate that Motivation has a positive and significant effect on commitment at PTPN II Sei Semayang. Job satisfaction has a positive and insignificant effect on commitment at PTPN II Sei Semayang. Motivation has a positive and significant effect on employee performance at PTPN II Sei Semayang. Satisfaction has a negative and insignificant effect on employee performance at PTPN II Sei Semayang. Commitment has a positive and insignificant effect on employee performance at PTPN II Sei Semayang. Motivation has a positive and insignificant effect on employee performance through commitment at PTPN II Sei Semayang. Satisfaction has a positive and insignificant effect on employee performance through commitment at PTPN II Sei Semayang.